DNA Binding Reorganizes the Intrinsically Disordered C-Terminal Region of PSC in Drosophila PRC1. Issue 17 (7th August 2020) - Kang, Jin Joo; Faubert, Denis; Boulais, Jonathan; Francis, Nicole J.
Abstract: Polycomb Group proteins regulate gene expression by modifying chromatin. Polycomb Repressive Complex 1 (PRC1) has two activities: a ubiquitin ligase activity for histone H2A and a chromatin compacting activity. In Drosophila, the Posterior Sex Combs (PSC) subunit of PRC1 is central to both activities. The N-terminal of PSC assembles into PRC1, including partnering with dRING to form the ubiquitin ligase. The intrinsically disordered C-terminal region of PSC compacts chromatin and inhibits chromatin remodeling and transcription in vitro . Both regions of PSC are essential in vivo . To understand how these two activities may be coordinated in PRC1, we used crosslinking mass spectrometry to analyze the conformations of the C-terminal region of PSC in PRC1 and how they change on binding DNA. Crosslinking identifies interactions between the C-terminal region of PSC and the core of PRC1, including between N and C-terminal regions of PSC. New contacts and overall more compacted PSC C-terminal region conformations are induced by DNA binding. Protein footprinting of accessible lysine residues reveals an extended, bipartite candidate DNA/chromatin binding surface in the C-terminal region of PSC. Our data suggest a model in which DNA (or chromatin) follows a long path on the flexible disordered region of PSC. Intramolecular interactions of PSC detected by crosslinking can bring the high-affinity DNA/chromatin binding region close to the core of PRC1 without disrupting the interface between the ubiquitin ligase and the nucleosome. Our approach may be applicable to understanding the global organization of other large intrinsically disordered regions that bind nucleic acids. Graphical abstract: Unlabelled Image Highlights: An intrinsically disordered region (IDR) in Polycomb protein PSC compacts chromatin. Crosslinking mass spectrometry (XL-MS) was used to analyze topology of the PSC IDR. Protein footprinting suggests a bipartite DNA binding surface in the PSC IDR. A model for the DNA-driven organization of the PSC IDR Combining XL-MS and protein footprinting is a strategy to understand nucleic acid binding IDRs.